Relasi Semantik Shadr, Qalb, Fu’ad, dan Lubb dalam Al-Qur’an: Kajian Tafsir Tematik atas Antropologi Batin Qur’ani - Muhammad Tajuddin (PT. Pustaka Andil Lestari, 2026)
This article examines the semantic relations among four Qur'anic terms that are often translated similarly as heart or inner self: shadr, qalb, fu’ad, and lubb. The main problem addressed is the tendency to flatten these terms into a single meaning, whereas the Qur'an employs each term with different lexical, rhetorical, theological, and psychological functions. This study uses qualitative library research with a thematic tafsir approach and semantic analysis of selected Qur'anic verses, classical Arabic lexicons, and representative classical and contemporary tafsir. The findings show that shadr refers to the inner space or chest that receives expansion, constriction, hidden impulses, and whispering; qalb functions as the central moral-cognitive faculty that understands, believes, changes, hardens, or becomes tranquil; fu’ad marks an intensified affective-cognitive state, especially in moments of shock, witnessing, or inner burning; and lubb denotes the purified core of reason reflected in the Qur'anic expression ulu al-albab. The study concludes that these terms form a graded Qur'anic anthropology of the inner human being and should not be reduced to a single translation.